The Creation of Eve - Conybeare, Catherine (Augustinian studies, 2018)
Why was Eve created? In De Genesi ad litteram, Augustine notoriously gives the answer that it was only causa pariendi, "for the sake of childbearing." Other late antique interpreters of Genesis emphasize the purpose of conjugal union and domesticity. But a fuller reading of Augustine's thoughts on the subject reveals the moment between the creation of Eve and the fall as pregnant with extraordinary possibility. This moment, of indeterminate length - for humans had not yet fallen into time - provides an opportunity for Augustine to unleash his theological imagination. This lecture is about paradise. It eschews the customary focus on Adam's paradisal desire to think about Eve's beginning. Augustine uses this beginning to emphasize the importance of sociality, and of marriage as its most perfect realization. He takes the quotidian miracle of childbirth as our closest intimation of God's act of creation. And he imagines new meanings for the trinity of Villanova's motto: ueritas, unitas, and caritas.